Unexplored potential in accounting research - Novrys Suhardianto; Dirgahayu Almi Mahati; Iman Harymawan; Dian Agustia (The Indonesian Accounting Review, 2024)
This study aims to find new ideas within the trends of accounting research. Using a literature review approach, this study maps the composition of accredited accounting research publications at SINTA 2 from 2020 to 2022 and specifically focuses on topics, methods, journals, authors and universities. The results of this study show that there is an increase in the number of published accounting articles, but it is not commensurate with the number of citations used, indicating that there is a decline in the quality of publication. Research topics are dominated by financial aspects, with the least attention given to AIS (Accounting Information Systems). The majority of research methods employ archival approaches, with experimental methods being the least utilized. This study notes that accounting research trends continue to be centralized on the island of Java, indicating the inequality in the distribution of resources and educational infrastructure across Indonesia. In addition, the results also show that undergraduate students still dominate research authors. This analysis provides an overview of the urgency of educational development in Indonesia.